The Association of Abuse and Depression With Suicidal Ideation in Chinese Adolescents: A Network Analysis - Li, Kuiliang; Zhan, Xiaoqing; Ren, Lei; Liu, Nan; Zhang, Lei; Li, Ling; Chen, Ting; Feng, Zhengzhi; Luo, Xi (Frontiers in Psychiatry, 2022)
Background: Abuse experiences in adolescents are associated with the risk of depression and suicide. Thus, there is an urgent need to develop prevention and intervention measures for clinicians, policy makers and researchers. Methods: Network analysis method was used to analyze the cross-sectional data of Chinese adolescents in this study. The Patient Health Questionnaire for Adolescents (PHQ-A) was used for assessing depression, item 9 of the PHQ-A was used to assess suicide ideation, and International Society for the Prevention of Child Abuse and Neglect (ISPCAN) Child Abuse Screening Tool-Children's Home Version (ICAST-CH) for assessing abuse. Results: The prevalence of suicidal ideation among Chinese adolescents was 21.46% (95% CI, 20.79%-22.16%). The prevalence of moderate or severe depression was 16.76%, and the prevalence of violence exposure, psychological victimization, neglect, physical victimization was 33.5%, 59.5%, 28.37% and 31.51% in the past years respectively. Network analysis results showed that the most central nodes in the network of abuse and depression were “unimportant”, “not cared”, and “pushed”. The bridge nodes were “suicidal ideation” and “unimportant”. The nodes “sadness”, “failure” and “unimportant” explained the largest proportion of the variance of suicidal ideation. Differences were found in the structure of both abuse and depression networks between adolescents with or without suicidal ideation. Limitations: The self-reporting-based cross-sectional surveys and community sample groups limit the inference of causality and the generalization of the results Conclusions: This study shows that “unimportant” is the central and bridge nodes in the abuse and depression networks, and also explains a part of variance of suicidal ideation. The effect of “unimportant” should be considered in the prevention and intervention of depression and suicide in adolescents with abuse experience. Future study is needed to confirm its role in clinical intervention.